Learning Styles: Humpty Dumpty revisited - Ivie, Stan (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2009)
AbstractWhat is a learning style? No one seems to know for sure. The language used by learning style theorists is filled with ambiguities. Price (2004) maintains that “learning style is often used as a metaphor for considering the range of individual differences in learning” (p. 681). Is learning style merely a fanciful metaphor or is it the wave of the future? The research offers mixed results. “Effects on improved test scores with testing conditions matched to student style have been published, but,” Curry (1990) adds, “there are also studies showing no discernible effect attributable to learning style variation” (p. 54). How many distinct learning style models are there? The Coffield (2004) team identified 71 different learning style models, which they subdivided into 13 major and 58 minor models. One of the most popular learning style models comes from Rita and Kenneth Dunn. They have developed an eclectic model featuring 21 (23) different variables that influence a person’s learning style. These variables run all the way from light and temperature to whether the person is analytic or global in his or her thinking. Rita Dunn says about the movement: “I want to convert the world” (Kortland, 2007, p. 8). And well she may. The Dunns’ model is used in the United States, Canada, Great Britain, Australia, and a number of other countries. Is learning style a panacea or a placebo? The jury is still out on that question.